Development and validation of the CAREGIVERS questionnaire: multi-assessing the impact of juvenile idiopathic arthritis on caregivers - Marcia Daniela Torres-Made; Ingris Peláez-Ballestas; Fernando García-Rodríguez; Ana Victoria Villarreal-Treviño; Brenda de Jesús Fortuna-Reyna; Manuel Enrique de la O-Cavazos; Nadina Eugenia Rubio-Pérez (BMC, 2020)
Abstract Background The primary caregiver is an important person in the life of patients with JIA. Their reactions depend on social, emotional and economic factors that affect the therapeutic alliance. Some generic instruments have been used to evaluate burden, anxiety, or quality of life of caregivers. This study aims to develop a specific instrument to measure the psychosocial and economic impacts on primary caregivers of patients with JIA. Methodology This is a mixed methods research, that includes qualitative and quantitative data, and was carried out in two phases. First phase: a pragmatic qualitative study (questionnaire construction) was conducted in two parts, a non-systematic literature review followed by interviews with primary caregivers. Second phase: a cross-sectional study (questionnaire validation) to complete validation and estimate Cronbach's alphas based on tetrachoric correlation coefficients, correlation matrix and Cohen's kappa coefficient test. Results There were 38 articles found related to the experience of caregivers. 15 primary caregivers were interviewed (female 93%, median age 45 years). Thematic analysis identified 9 important topics from the perspective of participants (economic impact, coping, family roles, impact of diagnosis, mental health, couple/mate relationships, impact at work, religion, and knowledge of the disease). These topics were combined to create the interview questionnaire (56 items). Later, it was modified to 62 items that were divided into five dimensions: impact of the disease (psychosocial, economic, family, and relationships), knowledge of the disease, alternative medicine, future, and religion. The interview questionnaire was applied to 32 primary caregivers (female 93%, median age 37 years), results identify depression on 29 (90%), 18 (56%) feel sadness at diagnosis, 20 (63%) mentioned that JIA has influenced in their financial situation, 23 (72%) feel anxiety about the future, and 11 (37%) considered that their family relationships have changed. Statistical analysis identified inconsistencies during convergent and divergent validity of the construct. Consequently, 11 items were eliminated, 3 relocated, 6 modified, and 39 compacted obtaining the "Impact of Pediatric Rheumatic Diseases on Caregivers Multi-assessment Questionnaire" (CAREGIVERS questionnaire). This final version resulted on an eight-dimension (28 items) instrument. Conclusions The CAREGIVERS questionnaire captures perspectives of both the participants and clinicians. It will be helpful to measure the impact of the disease and thus, to improve the quality of care of children with JIA and their families.